Color conversion film with ALD seal edge
By applying an inorganic sealing layer on the edge area of the color conversion film, edge sealing is achieved using ALD technology, which solves the edge intrusion problem and improves the stability and luminous performance of the film.
Patent Information
- Application Number
- CN202380058758.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-07-12
- Publication Date
- 2025-03-21
AI Technical Summary
The edge intrusion problem of existing color conversion films leads to degradation of color conversion materials at the edges, affecting the stability and luminous performance of the film.
A uniform and complete edge sealing is achieved by applying an inorganic sealing layer on the edge region of the color conversion film.
It effectively prevents the diffusion of moisture and oxygen, reduces edge intrusion, and improves the overall stability and luminous performance of the color conversion film.
Smart Images

Figure CN119678098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of color conversion films suitable for use in display backlight assemblies and light emitting devices. The present invention particularly provides color conversion films with edge seals, thereby imparting improved stability to such films. Furthermore, the present invention relates to a new manufacturing method to obtain edge sealed color conversion films. Background Art
[0002] Color conversion films are known and widely used in industry, for example in LCD backlights. Such films contain green and / or red color conversion materials that emit green and red light, respectively, when excited by blue light. Such films are produced on roll-to-roll coating equipment, producing a roll of color conversion film. Finally, rectangular pieces having the approximate size of a corresponding LCD display are cut from the color conversion film roll by, for example, die cutting or laser cutting. The resulting cut edges of the rectangular-shaped color conversion film expose the color conversion material in the QD film to air. The cut edges of such color conversion films include defects such as fine cutting cracks or other irregularities.
[0003] It is well known that color conversion films are sensitive to air and moisture. Usually, the main surface of such films is therefore covered with a protective layer. In this context, Nehm et al. (ACS Appl. Mater. Interfaces 2015, 7, 22121-22127) discussed ultrathin ALD deposited AlOx films. The authors observed that these AlOx films are unstable if directly exposed to ambient relative humidity and quickly lose their protective properties. To address this drawback, an additional coating (preferably glued on a PET foil) provides a low temperature of 2×10 -5 g(H2O)m -2 d -1 Obviously, this method may be suitable for the main surface of the film, but not for the edge of such a film.
[0004] Edge ingress is a known problem in the industry and is discussed, for example, in Nelson et al. (TechConnect Breif 2015, ISBN 978-1-4987-4727-1, pages 282 to 285). In short, color conversion materials (particularly quantum dots and perovskite crystals) degrade at the edges of such films due to the diffusion of moisture and / or oxygen into the film starting from the edge. This results in the so-called edge ingress, which is the distance from the edge towards the center of the film at which the green and / or red color conversion materials degrade and no longer emit light or emit much less light. Nelson et al. acknowledge the problem of edge ingress but do not make any suggestions on how to solve the problem.
[0005] Kim et al. (US2020 / 0209463) discloses a light guide plate and a display device including the same. In this context, a sealed color conversion film is described. The seal disclosed in this document has a non-uniform thickness and does not allow for proper control of edge intrusion.
[0006] In addition, Skipor et al. (US9470399) discloses a light-emitting polymer film, a display including the same, and its manufacture. Its side surface is protected by a barrier layer. It is suggested to form such a barrier by transfer molding.
[0007] In addition, Luechinger et al. (EP3936585) discloses a self-supporting film and a light-emitting device. This document does not mention edge sealing.
[0008] In addition, Chu (US2020 / 0251529) discloses a display device in which edge portions are sealed by thermal curing using laser technology.
[0009] In addition, Lee et al. (US2019 / 0154901) disclosed a light guide panel including a passivation layer on the edge of the wavelength conversion layer, and suggested using CVD to obtain the light guide panel.
[0010] Finally, Fang et al. (Adv. Optical Mater., 2020, 8, 1902118) discussed combining sol-gel and ALD methods to encapsulate quantum dots to obtain a multilayer coating of SiO2 and Al2O3 on the QDs. Summary of the invention
[0011] The present invention aims to overcome one or more disadvantages of the prior art. In particular, the present invention addresses the need for a color conversion film having improved stability over its entire surface area. This is achieved by avoiding or at least reducing edge intrusion of the color conversion film.
[0012] In particular, the object is achieved by providing an edge-sealed color conversion film as defined in claim 1 and by providing a manufacturing method as defined in claim 9. Further aspects of the invention are disclosed in the description and the independent claims, preferred embodiments are disclosed in the description and the dependent claims.
[0013] The present invention will be described in more detail below. It should be understood that the various embodiments, preferred embodiments and scopes provided / disclosed in this specification may be combined arbitrarily. In addition, depending on the specific embodiment, the selected definition, embodiment or scope may not be applicable.
[0014] Unless otherwise stated, the following definition Should apply to this manual:
[0015] Unless otherwise stated herein or the context clearly contradicts, the terms "a", "an", "the" and similar terms used in the context of the present invention should be interpreted as covering both the singular and the plural. The term "comprising / including" should include all, "comprising / including", "essentially consisting of..." and "consisting of...". Unless otherwise stated herein or the context clearly contradicts, percentages are given in weight %. "Independently" means that a substituent / ion can be selected from one of the specified substituents / ions, or can be a combination of more than one of the above substituents / ions.
[0016] A "film" is a thin structure that includes one or more layers (a "laminate") and includes two major surfaces separated by an edge. Top film region: The top film region describes the upper surface of the color conversion film. Bottom film region: The bottom film region describes the surface of the color conversion film at the bottom opposite the top film region. The top film region and the bottom film region are also collectively referred to as "major surface regions". Edge regions: The first edge region, the second edge region, the third edge region, and the fourth edge region describe the region of each of the four edges of a rectangular shaped color conversion sheet. For a disc shaped film, a single edge separates the top film region and the bottom film region.
[0017] The term "color conversion material" is known in the art and in the context of the present invention relates to a material which emits light in the visible range when excited by blue light. In the context of the present invention, it is preferred that the color conversion material emits red or green light. The color conversion material may be organic (polymer or small organic molecule) or inorganic. The inorganic color conversion material is preferably selected from the list of luminescent crystals, quantum dots, perovskite crystals or micrometer-sized phosphors, most preferably perovskite crystals and quantum dots.
[0018] The term "luminescent crystal" (LC) is known in the art and in the context of the present invention refers to a crystal of 2 nm to 100 nm made of a semiconductor material. The term includes quantum dots, typically in the range of 2 nm to 10 nm, and nanocrystals, typically in the range of 10 nm to 100 nm.
[0019] As the term indicates, LCs exhibit luminescence. In the context of the present invention, the term luminescent crystals includes both single crystals and polycrystalline particles. In the latter case, a particle may consist of several domains (grains), connected by crystalline or amorphous phase boundaries. Luminescent crystals are semiconductor materials that exhibit a direct band gap (usually in the range of 1.1 eV to 3.8 eV, more typically 1.4 eV to 3.5 eV, and even more typically 1.7 eV to 3.2 eV). When irradiated with electromagnetic radiation equal to or higher than this band gap, valence band electrons are excited to the conduction band, leaving electron holes in the valence band. The excitons (electron-electron hole pairs) formed then radiatively recombine in the form of photoluminescence, with the maximum intensity concentrated near the LC band gap value and exhibiting a photoluminescence quantum yield of at least 1%. When in contact with an external source of electrons and electron holes, LCs can exhibit electroluminescence.
[0020] The term "quantum dot" (QD) is known and particularly relates to semiconductor nanocrystals with a diameter typically between 2nm and 10nm. Within this range, the physical radius of the QD is smaller than the bulk excitation Bohr radius, resulting in a dominance of quantum confinement effects. As a result, the electronic state of the QD and therefore the band gap is a function of the QD composition and physical size, i.e. the color of absorption / emission is related to the QD size. The optical quality of a QD sample is directly related to its uniformity (a more monodisperse QD will have a smaller emission FWHM). When the QD reaches a size greater than the Bohr radius, the quantum confinement effect is hindered and the sample may no longer emit light because the non-radiative path of exciton recombination may become dominant. Therefore, QDs are a specific subset of nanocrystals, particularly defined by their size and size distribution. Typical quantum dot compositions contain cadmium or indium, for example in the form of cadmium selenide (CdSe) or indium phosphide (InP).
[0021] The term "core-shell quantum dots" is known and relates in particular to quantum dots that typically comprise an indium-containing or cadmium-containing core, typically having a CdSe core or an InP core, with an additional shell that typically comprises zinc sulfide (ZnS), zinc selenide (ZnSe), cadmium sulfide (CdS) or a combination thereof. Core-shell quantum dots may comprise multiple shells or a shell gradient.
[0022] The term "perovskite crystal" is known and includes in particular crystalline compounds of the perovskite structure. Such perovskite structures are known per se and are described as cubic, pseudo-cubic, tetragonal or orthorhombic crystals with the general formula M 1 M 2 X3, where M 1 It is a cation with coordination number 12 (cuboctahedral), M 2is a cation with coordination number 6 (octahedral), and X is an anion in a cubic, pseudo-cubic, tetragonal or orthorhombic position of the lattice. In these structures, selected cations or anions can be replaced by other ions (randomly or regularly up to 30 atomic %), thereby producing doped perovskites or non-stoichiometric perovskites, still retaining their original crystal structure. Preferably, the luminescent perovskite crystals are approximately equiaxed (e.g., spherical or cubic). If the aspect ratio of all 3 orthogonal dimensions (longest direction: shortest direction) is 1 to 2, the particles are considered to be approximately equiaxed. Therefore, the components of the LC preferably contain 50% (n / n) to 100% (n / n), preferably 66% (n / n) to 100% (n / n), more preferably 75% (n / n) to 100% (n / n) equiaxed nanocrystals. The production of such light-emitting perovskite crystals is known, for example from WO 2018 / 028869, which is incorporated by reference.
[0023] The term "micrometer-sized phosphors" is known and includes in particular K2SiF6:Mn 4+ (KSF).
[0024] The term "polymer" is known and includes organic and inorganic synthetic materials comprising repeating units ("monomers"). The term polymer includes homopolymers and copolymers. In addition, crosslinked polymers and non-crosslinked polymers are also included. Depending on the context, the term polymer should include its monomers and oligomers. For example, polymers include acrylate polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, urethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers, norbornene polymers, silazane polymers, organosilicon polymers and cycloolefin copolymers. As conventional in the art, polymers may include other materials, such as polymerization initiators, stabilizers and fillers.
[0025] The term "color conversion film" is known in the art. Color conversion films find wide application in commercial items such as displays. According to the present invention, such films contain red and / or green color conversion materials. According to the present invention, such films convert blue light partially or completely into red and / or green light. Typically, blue light is partially converted, resulting in emission of light in the blue, green and / or red spectrum. When adjusting the intensity of the blue light and the concentration, film thickness and amount of luminescent green and / or red material, the color of the emitted light can be adjusted according to the needs of the customer.
[0026] Such a color conversion film can be described as a laminate structure and identified by its individual layers, such as a "light-emitting polymer layer", a "red-emitting polymer layer", a "green-emitting polymer layer", a "first set of covering layers", a "second set of covering layers", an "inorganic sealing layer", and optionally a "non-emitting polymer layer".
[0027] Furthermore, such color conversion films can be identified by their individual surface areas, for example “top film area”, “bottom film area”, “first edge area”, “second edge area”, “third edge area”, “fourth edge area”.
[0028] Color conversion films typically have a film thickness (including all individual layers) of 10 to 500 microns, preferably 20 to 250 microns, most preferably 30 to 200 microns.
[0029] refer to Attached photos The invention will be better understood. In these drawings, the following reference list applies:
[0030] 010 Color conversion film
[0031] 010`Native color conversion film, i.e., without edge sealing layer
[0032] 011 First Marginal Area
[0033] 013 Second marginal area
[0034] 012 The Third Marginal Area
[0035] 014 The Fourth Marginal Area
[0036] 020 Color conversion film stack
[0037] 021 Top membrane area
[0038] 022 Bottom membrane area
[0039] 030 Edge sealing layer (sealing layer on all edges of native film 010`)
[0040] 030` surface sealing layer (sealing layer covering the two main surfaces of the original membrane 010`)
[0041] 040 Free volume accessible to ALD process gases (e.g. gaseous metal organic reactants and purge gases)
[0042] 050 ALD Room
[0043] 070 Another layer
[0044] 080Color conversion material that converts blue light into light with a longer wavelength
[0045] 090 Luminescent polymer layer
[0046] 100 Green color conversion material
[0047] 110 Green luminescent polymer layer
[0048] 200 Red color conversion material
[0049] 210 Red-luminescent polymer layer
[0050] 121 The first set of covering layers
[0051] 122 Second set of covering layers
[0052] Figure 1 A rectangular native color conversion film is shown in perspective view before the edge treatment of the present invention. The major surface areas are indicated as 022 and 021 and the edges are indicated as 011 ... 014.
[0053] Figure 2 Rectangular color conversion film 010 is shown in top view after the edge treatment of the present invention; sealing layer 30 (not to scale) and native film 010 ′ (color conversion material not shown) are labeled.
[0054] The enlarged portion at the top right shows complete and defect-free edge coverage: the inorganic sealing layer uniformly covers the cracks in the film 010', thus preventing oxygen and / or H2O from diffusing into the color conversion film.
[0055] The enlarged portion at the bottom right shows an incomplete and defective edge coverage for comparison: the inorganic sealing layer, when deposited by a directional vapor deposition technique (eg CVD, PVD). Due to the shadowing effect, the cracks in the film 010' are not uniformly coated.
[0056] FIG. 3 shows various color conversion films of the present invention in side view, thereby illustrating potential laminate structures.
[0057] 3a: Figure 2 Such a film will usually receive further processing of the two main surfaces 021 and 022, such as applying a cover layer 120, 121, to obtain, for example, Figure 3b The laminated film structure shown.
[0058] 3b: Figure 2 A film having an additional conventional covering layer (such as a barrier film) on the main surface.
[0059] 3c: Figure 3b A film in which two different types of color conversion materials are in one layer, see Example 3.
[0060] 3d: Figure 2 A film in which two different types of color conversion materials are in two separate layers, see Example 1.
[0061] Figure 4The manufacturing setup of the inventive film 010 is shown. A stack 020 of color conversion films (comprising a plurality of individual native films 010') is located in an ALD chamber 040. The stack 020 is adapted to seal as many edges of the color conversion films as possible in one ALD batch, and secondly to reduce the contact of the ALD process gases with the major surfaces (except the top surface of the stack 020). This setup allows sealing of all edges, but no or very limited sealing of the major surfaces, as shown on the right, thereby obtaining a plurality of inventive edge-sealed color conversion films 010.
[0062] Figure 5 A rectangular color conversion film 010 is shown in top and side views after the edge and major surface have been subjected to the treatment of the invention, i.e. cut along the horizontal dashed line. The seal layer 30 (not to scale) and the native film 010' are labeled. As shown, the seal layer thickness on the edge and major surface can be different. In the embodiment shown, the edge seal has a lower thickness than the major surface seal.
[0063] FIG. 6 shows various color conversion films of the present invention in side view, illustrating a potential laminate structure sealed on all edges and both major surfaces with a sealing layer 30 of the present invention (again not to scale).
[0064] 6b: Simple membrane, coated on edges and main surfaces
[0065] 6c: A membrane as in 6b, but with additional conventional cover layers 122 and 121
[0066] 6d: Film as in 6c, but with two different types of color conversion materials 100 and 200
[0067] 6e: A membrane as in 6d, but with only one set of conventional covering layers
[0068] 6f: Film as in 6d, but the red-emitting layer and the green-emitting layer are separated into separate layers 110 and 210
[0069] 6g: A membrane as in 6f, but with only one set of conventional cover layers 121
[0070] 6h: Film as in 6b, but the red-emitting layer and the green-emitting layer are separated in separate layers 110 and 210
[0071] Figure 7A manufacturing setup for a film 010 of the present invention including a sealing layer on all edges and both major surfaces as shown in FIG6 is shown. A stack 020' of improved color conversion films (comprising a plurality of individual native films 010') is located in an ALD chamber. The stack 020' is adapted to allow ALD process gases to contact the major surfaces and edges. This setup allows sealing of all edges 030 and sealing of major surfaces 030', as shown on the right, thereby obtaining a plurality of edge-sealed and face-sealed color conversion films 010 of the present invention.
[0072] Figure 8 Shown with Figure 7 Compare alternative manufacturing setup for the inventive film 010. The edge sealed film is subjected to an additional ALD step.
[0073] Fig. 9 A film 10 of the invention is shown which comprises a further layer 070 , such layer 070 being devoid of an edge seal 030 .
[0074] In a first aspect, the invention relates to a color conversion film 010 that emits light in the visible range, preferably red and / or green light, when excited by blue light. Such a film comprises a native film (010', without edge seal) having two main surfaces 021, 022 and at least one edge 011...014, and contains a color conversion material 80, 100, 200. Such a film also comprises an inorganic sealing layer 030 on all edge regions, whereby the inorganic sealing layer is an atomic layer deposition layer that completely covers all edge regions with very high thickness uniformity. This aspect of the invention will be further described in detail below.
[0075] Edge Sealing Layer 030:
[0076] In the context of the present invention, the sealing layer 030 has the following properties:
[0077] The edge sealing layer 030 completely covers the edges of the film 010' without defects or pinholes. "Complete and defect-free" coverage can be inferred from the stability of the color conversion film after accelerated degradation tests. The term "complete and defect-free coverage" is chosen to distinguish from incomplete and defective coatings obtained, for example, by directional vapor deposition techniques (e.g. CVD, PVD). Due to shadowing effects, such directional vapor deposition techniques cannot ensure "complete and defect-free coverage" of the surface.
[0078] The thickness of the edge seal layer 030 is from 1 nm to 500 nm, preferably from 3 nm to 200 nm, and most preferably from 10 nm to 100 nm. In an embodiment, their thickness is from 2 nm to 90 nm. In another embodiment, their thickness is from 5 nm to 50 nm. They have a very uniform thickness over the entire coated substrate, characterized in that the standard deviation of the thickness variation over the entire substrate is less than 10%, preferably less than 3%, and most preferably less than 1%. The thickness of the inorganic sealing layer can be determined by transmission electron microscopy (TEM), preferably on a sample prepared by a microtome. Without being bound by theory, it is believed that its thickness and standard deviation are characteristics of the ALD manufacturing steps described herein.
[0079] The edge sealing layer 030 comprises an inorganic material, in particular, consists of an inorganic material. The term "inorganic material" is known in the art. In view of the ALD manufacturing method described below, the preferred inorganic material is selected from the group of metal oxides or metal nitrides. More preferably, it is selected from silicon oxide, aluminum oxide, zirconium oxide, hafnium oxide or titanium oxide (e.g., SiO x , x = 1.9 to 2.1; AlO x , x = 1.4 to 1.6; TiO x , x=1.9 to 2.1; ZrO x , x = 1.9 to 2.1; HfO x , x = 1.9 to 2.1). They can consist of only one inorganic material or more than one inorganic material (e.g., a multilayer of different inorganic layers with different chemical compositions). ALD manufacturing produces very pure inorganic layers. However, there may be some residual organic material from the precursor material. Therefore, a layer of inorganic material refers to a purity of >95 wt%, typically >99 wt%, for example >99.5 wt%. The composition of the inorganic sealing layer can be determined by X-ray photoelectron spectroscopy (XPS) or TEM equipped with EDX spectroscopy (EDX analysis of a cross section of the inorganic sealing layer).
[0080] When ALD manufacturing is applied to the film edges 011 ... 014, some inorganic material may be deposited on the main surfaces 021, 022. This will produce an additional coating on part of the main surface. Such a partial coating on the main surface does not negatively impart film properties and is covered by the present invention. This partial coating is not shown in the schematic diagrams discussed herein.
[0081] In one embodiment, the inorganic sealing layer consists of alternating layers of two different metal oxides, whereby preferably the number of individual metal oxide layers is greater than two, more preferably greater than three, most preferably greater than five.
[0082] In other embodiments, the inorganic sealing layer comprises alternating layers of the following different metal oxide combinations:
[0083] ·AlOx / TiOx
[0084] ·AlOx / SiOx
[0085] ·AlOx / ZrOx
[0086] ·AlOx / HfOx
[0087] TiOx / SiOx
[0088] Thus preferably, the thickness of the first designated oxide layer is 3 nm to 100 nm (preferably 10 nm to 50 nm), and preferably, the thickness of the second designated oxide layer is 2 nm to 50 nm.
[0089] (Preferably 5nm to 20nm).
[0090] In a further embodiment, the inorganic sealing layer comprises the following layer sequence:
[0091] -AlO x / MO x , where M = Si, Zr, Ti, Hf
[0092] Thus preferably, the thickness of the aluminum oxide layer is 3 nm to 100 nm (preferably 10 nm to 50 nm), and preferably MO x The thickness of the layer is from 2 nm to 50 nm (preferably from 5 nm to 20 nm).
[0093] Preferably, the inorganic sealing layer is applied to the edges and optionally the main surfaces of the film by atomic layer deposition (ALD) technology. ALD is a coating technology known per se, but has not been applied in the context described herein. Therefore, the present invention also provides a color conversion film 010, which emits light in the visible light range, preferably red and / or green light when excited by blue light. Such a film comprises a native film (010', without edge seal) having two main surfaces 021, 022 and at least one edge 011...014, and contains a color conversion material 80, 100, 200. Such a film also includes an inorganic sealing layer 030 on all edge areas, whereby the inorganic sealing layer is an ALD-deposited inorganic layer covering all edge areas.
[0094] Surface sealing layer 030`:
[0095] In the context of the present invention, in addition to the edge sealing layer 030 covering all edges, there may be one or two sealing layers 030' (covering one or both main surfaces). If present, such surface sealing layers 030' have the following characteristics:
[0096] • They completely cover one or both major surfaces of the film 010' without defects or pinholes.
[0097] • Their thickness is from 1 nm to 500 nm, preferably from 3 nm to 200 nm, most preferably from 10 nm to 100 nm.
[0098] They have a very uniform thickness across the coated substrate, characterized by a standard deviation of the thickness variation across the substrate of less than 10%, preferably less than 3%, most preferably less than 1%.
[0099] • They comprise, in particular consist of, inorganic materials.
[0100] With regard to the above-mentioned properties of the surface sealing layer 030 ′, in particular the definition of the inorganic material, defect-free coverage, layer structure, thickness and its standard deviation, the same considerations apply as for the edge seal 030 described above.
[0101] In an embodiment, the average thickness of the surface seal 030 ′ is lower than the average thickness of the edge seal 030 , for example, at least 1 / 2 lower, preferably at least 4 / 5 lower.
[0102] Color conversion materials:
[0103] The term color converting material is as defined above.
[0104] In one embodiment of the present invention, the red color conversion material emits red light (630nm+ / -30nm) in response to being excited by shorter wavelength light, and is preferably selected from core-shell quantum dots or perovskite crystals. The core-shell quantum dots are preferably selected from core-shell quantum dots containing indium or cadmium (most preferably indium).
[0105] The green color conversion material emits green light in response to being excited by shorter wavelength light (500-550 nm, particularly concentrated around about 525-535 nm), and is preferably selected from core-shell quantum dots or perovskite crystals, preferably perovskite crystals.
[0106] The perovskite crystals are selected from compounds of formula (I):
[0107] [M 1 A 1 ] a M 2 b X c (I) where:
[0108] A 1 represents one or more organic cations, especially formamidine (formamidinium, FA),
[0109] M 1 represents one or more alkali metals, in particular cesium,
[0110] M 2 Indicates one or more different from M 1 of metals, especially Pb,
[0111] X represents one or more anions selected from halides, pseudohalides and sulfides, in particular Br,
[0112] a represents 1 to 4,
[0113] b means 1 to 2,
[0114] c represents 3 to 9, and
[0115] Among them, there is M 1 or A 1 , or M 1 and A 1 .
[0116] In a further advantageous embodiment of the present invention, the green emitting crystal is a green emitting perovskite crystal of formula (I'): FAPbBr3(I').
[0117] In particular, formula (I), (I') describes a perovskite luminescent crystal which, after absorbing blue light, emits light with a wavelength between 500 nm and 550 nm in the green light spectrum, particularly concentrated around 525 nm to 535 nm.
[0118] Luminescent polymer layer 090:
[0119] The light emitting polymer layer 090 comprises a color conversion material 080 (preferably red and / or green) distributed within a polymer. Suitable color conversion materials 080 are as defined above. Suitable polymers may be selected from the group of acrylates, methacrylates, epoxies, silazanes, urethanes, preferably acrylates and methacrylates. In an embodiment, such polymers are cross-linked. In an embodiment, a combination / blend of more than one polymer is used. Suitably, the light emitting polymer layer has a thickness of 10 microns to 200 microns, preferably 20 microns to 100 microns.
[0120] Green emitting polymer layer 110:
[0121] The green-emitting polymer layer comprises a polymer and a green color conversion material 100 distributed within such polymer.
[0122] Suitable green color conversion material 100 may be selected from the group of perovskite crystals and core-shell quantum dots containing indium; perovskite crystals are preferred.
[0123] Suitable polymers may be selected from the group of acrylates, methacrylates, epoxies, silazanes, urethanes, preferably acrylates and methacrylates. In an embodiment, such polymers are cross-linked. In an embodiment, a combination / blend of more than one polymer is used.
[0124] Suitably, the thickness of the green-emitting polymer layer is from 10 micrometers to 200 micrometers, preferably from 20 micrometers to 100 micrometers.
[0125] Red luminescent polymer layer 210:
[0126] The red-emitting polymer layer comprises a polymer and a red color conversion material 200 distributed within such polymer.
[0127] Suitable red color conversion materials 200 include red perovskite crystals or core-shell quantum dots containing indium, preferably core-shell quantum dots containing indium.
[0128] Suitable polymers may be selected from the group of acrylates, methacrylates, epoxies, silazanes, urethanes, preferably acrylates and methacrylates. In an embodiment, the polymer is cross-linked. In an embodiment, a combination / blend of more than one polymer is used. In an embodiment, the polymer comprises a monofunctional multicyclic acrylate or methacrylate and a multifunctional acrylate or methacrylate.
[0129] Suitably, the thickness of the red-luminescent polymer layer is from 10 micrometers to 200 micrometers, preferably from 20 micrometers to 100 micrometers.
[0130] The first and second groups of covering layers 121, 122:
[0131] Adjacent to the light emitting polymer layer, there may be covering layers 121, 122. The first set of covering layers and the second set of covering layers may each independently comprise a single layer or a plurality of layers, whereby such layers may be inorganic or polymeric and non-emissive (meaning that they do not emit light when excited by blue light). The covering layers may have different functions and may be selected from:
[0132] Barrier film / layer
[0133] Intermediate film / layer
[0134] Adhesive film / layer
[0135] Light management films / layers
[0136] Non-emissive polymer film / layer
[0137] Barrier film / layer: In the context of the present invention, the barrier film exhibits a low permeability to oxygen and / or moisture. Such a barrier film may be selected from inorganic barrier films or polymeric barrier films having an oxygen transmission rate (OTR) of less than 10 cm3 / m2*day, preferably less than 1 cm3 / m2*day, most preferably less than 0.1 cm3 / m2*day, and / or a water vapor transmission rate (WVTR) of less than 10 g / m2*day, preferably less than 1 g / m2*day, most preferably less than 0.1 g / m2*day. The OTR is determined by ISO 15105 at a temperature of 23°C / 90% rh and atmospheric pressure. The WVTR may be determined by ISO 15106-3:2003 at a temperature / relative humidity of 40°C / 90% rh.
[0138] The inorganic barrier film comprises or consists of a continuous layer of an inorganic material. Typically, the thickness of such a layer is from 1 nm to 10 microns, preferably from 10 nm to 1 micron. Suitable inorganic materials include, but are not limited to, SiO x (x = 1.7 to 2.3), AlO x (x = 1.3 to 1.7) and Si x N y (x=3, and y=3.5 to 4.5).
[0139] The polymer barrier film consists of a polymer or polymer blend and has a typical thickness of 5 to 200 microns, preferably 10 to 100 microns, most preferably 20 to 50 microns.
[0140] The inorganic barrier films and polymer barrier films may be commercial items and may be supported by another polymer substrate.
[0141] Intermediate films / layers: Intermediate layers may be implemented in the color conversion film to further improve the stability of the color conversion material (typically perovskite crystals), separate specific layers to avoid contact of such specific layers, or facilitate the manufacture of the color conversion film, for example to reduce manufacturing costs.
[0142] The intermediate layer comprises a polymer or consists of a polymer. Suitable polymers are selected from the list of acrylate or methacrylate polymers, epoxy polymers, silazane polymers, cycloolefin copolymers, polyesters, preferably acrylate polymers or methacrylate polymers. In an embodiment, such polymers are crosslinked.
[0143] The thickness of the intermediate layer is from 5 micrometers to 100 micrometers, preferably from 10 micrometers to 80 micrometers, and most preferably from 20 micrometers to 60 micrometers.
[0144] Adhesive films / layers: Such layers are known in the art and may be included in the color conversion film to improve compatibility between layers, or to improve adhesion between layers, or to facilitate manufacturing.
[0145] Typically, such layers are used on barrier films to improve the adhesion of adjacent polymer layers, such as interlayers or light-emitting polymer layers.
[0146] Typical thicknesses of such layers are from 0.1 micrometer to 20 micrometers, preferably from 0.5 micrometer to 10 micrometers, most preferably from 1 micrometer to 5 micrometers.
[0147] In an embodiment, such a layer consists of a polymer or a polymer blend.
[0148] Typical polymers are selected from the list of acrylate or methacrylate polymers, epoxy polymers, urethane polymers.
[0149] Light Management Films / Layers: Light management films / layers are sometimes used in color conversion films, for example to increase the light output of the color conversion film or to reflect a specific portion of the light.
[0150] Light management films include prism films, brightness enhancement films, micro lens array (MLA) films (such films are provided, for example, by Brightview Technologies), and blue light pass filter films (also called dichroic mirror films; such films transmit blue light and reflect green and red light; such films are provided by 3M and are used in Apple iPadPro XDR starting in 2021).
[0151] The thickness of MLA films is typically 10 to 50 microns.
[0152] The thickness of the dichroic mirror film is typically 20 microns to 100 microns.
[0153] Membrane geometry:
[0154] In one embodiment, the color conversion film has a rectangular shape. The length and width of such a film are similar to a typical LCD display, for example ranging from mobile phone size to TV size. This includes aspect ratios of 4:3, 3:2, 16:9 or 3:1 and diagonals of 5 cm to 250 cm.
[0155] As is conventional in the art, the rectangular shaped film may include slight deviations from a "rectangle" in the strict geometric sense. For example, the edges may be rounded or there may be notches to adapt the film to its intended use or to facilitate the manufacture of the device. In an embodiment, the color conversion film has a rectangular shape with rounded corners. Such rounded edges typically have a radius of <5 mm. In an embodiment, the edge of the rectangular shaped color conversion film exhibits one or more small geometric features that protrude slightly from the edge (such edge features, also referred to as "notches", are implemented in the edge to keep the color conversion film in the display backlight in place and avoid undesirable rearrangement of the film). It was found that the method of the present invention for edge seals is also applicable to such rounded edges and edges with additional geometric features. This is considered to be an additional benefit of the method of the present invention described below.
[0156] In an embodiment, the color conversion film is disc-shaped, thereby having only one edge 011 separating major surfaces 021 and 022. The inventive method for edge seals was found to be applicable to such unconventional shapes as well.
[0157] Membrane structure:
[0158] Within the scope of the present invention, a variety of laminate structures (film structures) can be realized. These structures share the common feature that at least the light-emitting polymer layer 090, 110, 210 is sealed with an inorganic sealing layer 030 on all edges.
[0159] refer to Figure 1 and 2 , the color conversion film 010 comprises an inorganic sealing layer 030 on all four edge regions 011 . . . 014, whereby the inorganic sealing layer completely covers all four edge regions and whereby the thickness standard deviation including all four edges is less than 10%, preferably less than 3%, and most preferably less than 1%.
[0160] refer to Figures 3a to 3d , the color conversion film 010 includes an inorganic seal 030 ("edge seal") covering all edges. In this embodiment, the film has no or substantially no inorganic coating on its major surface. This is achieved by providing a stack 20 in which direct contact of the films 010' is provided, or in which the films 010' are separated by auxiliary separation films. The skilled person is aware that due to the diffusion effect of the ALD process gases, manufacturing via ALD deposition may still produce some inorganic coverage on the major surfaces. However, such a diffusion process will not produce complete coverage of the major surfaces. To reflect this, the term no or substantially no coating is selected. When following the method according to Figure 4 Such an implementation scheme can be obtained when an ALD process is performed.
[0161] refer to Figures 6b to 6g In addition to the inorganic seal 030 ("edge seal") covering all edges, the color conversion film 010 also has an inorganic seal 030' ("surface seal") covering both major surfaces.
[0162] In an embodiment, the average thickness of the surface seal 030' is lower than the average thickness of the edge seal 030 (at least 1 / 2 lower; preferably 4 / 5 lower). Figure 8 Such an implementation scheme can be obtained when an ALD process is performed.
[0163] In an embodiment, the surface seal 030' and the edge seal 030 have substantially the same thickness, with a difference of less than 10%, preferably less than 3%, and most preferably less than 1%. In this embodiment, the film thickness can be in the range of 1nm to 500nm, preferably 10nm to 100nm. When following the method according to Figure 7 Such an implementation scheme can be obtained when an ALD process is performed.
[0164] Preferably, both native color conversion film 010' and the inventive color conversion film 010 are freestanding films. The inventive film has improved properties when assembled into a display device.
[0165] refer to Fig. 9 , within the scope of the present invention, the color conversion film 010 of the present invention (including edge seal 030 and optionally surface seal 030') may thus additionally include one or more layers (additional layers 070) at the top and / or bottom. Such additional layers do not include an inorganic sealing layer on the edge region. If present, such additional layers may be any layer selected from the following:
[0166] Glass substrate
[0167] Barrier film / layer
[0168] Intermediate film / layer
[0169] Adhesive film / layer
[0170] Light management films / layers
[0171] Non-emissive polymer film / layer
[0172] If the finishing step (d) is a further lamination step, this embodiment showing the further layer 070 can be obtained.
[0173] Advantageous embodiments:
[0174] In light of the present disclosure, the following inventive membrane 010 is considered to be particularly advantageous.
[0175] In one embodiment, the color conversion film comprises only one type of color conversion material 080, either a red color conversion material 200 or a green color conversion material 100, preferably a green color conversion material. (See e.g. Figure 3a , 3b , 6b, 6c, 9)
[0176] In another embodiment, the color conversion film comprises a green color conversion material and a red color conversion material. (See e.g. Figure 3c , 6d )
[0177] In another embodiment, the color conversion film comprises a green color conversion material selected from the following list: perovskite crystals, core-shell quantum dots containing indium or core-shell quantum dots containing cadmium, preferably perovskite crystals.
[0178] In another embodiment, the color conversion film comprises a red color conversion material selected from the following list: perovskite crystals, core-shell quantum dots containing indium, or core-shell quantum dots containing cadmium, preferably core-shell quantum dots containing indium or perovskite crystals, and most preferably core-shell quantum dots containing indium.
[0179] In another embodiment, the color conversion film comprises a green color conversion material selected from perovskite crystals and a red color conversion material selected from indium containing core-shell quantum dots.
[0180] In another embodiment, the green color conversion material and the red color conversion material are present in different polymer layers; the green color conversion material is present in a polymer layer that emits green light, and the red color conversion material is present in one or more polymer layers that emit red light. (See e.g. Figure 6f , 3d )
[0181] In another embodiment, the color conversion film includes a first set of covering layers and a second set of covering layers, whereby the color conversion material is located between the two sets of covering layers. (See e.g. Figure 3b , 3c , 3d)
[0182] In another embodiment, the color conversion film comprises a first set of cover layers and a second set of cover layers, whereby the color conversion material is located between the two sets of cover layers, and whereby the two sets of cover layers each comprise at least one barrier film, preferably at least one inorganic barrier film.
[0183] In another embodiment, color conversion film 010 includes edge seal 030 and surface seal 030', but no additional layers 070, 121, 122. (See e.g. Figure 6b and 6g )
[0184] In another embodiment, color conversion film 010 includes edge seal 030 and surface seal 030' and a set of cover layers 121 or 122. (See e.g. Figure 6e ). Preferably, one set of covering layers 121 or 122 comprises or consists of a polymer film, most preferably consists of a PET film.
[0185] In another embodiment, the color conversion film comprises one or more intermediate layers or one or more adhesive layers between the one or more light emitting polymer layers and the one or more sets of cover layers.
[0186] In another embodiment, a color conversion film includes a green emitting polymer layer and a red emitting polymer layer separated by one or more inorganic barrier films.
[0187] In another embodiment, the color conversion film comprises a green emitting polymer layer and a red emitting polymer layer separated by a polymer film, preferably a PET film.
[0188] In another embodiment, the color conversion film includes a dichroic mirror film (blue light pass filter film) in one of the first or second set of cover layers 121 , 122 .
[0189] In another embodiment, the color conversion film includes a microlens array film (MLA) in one of the first or second set of cover layers 121 , 122 .
[0190] In another embodiment, the color conversion film includes a dichroic mirror film (blue light pass filter film) in cover layer 121 and a microlens array film (MLA) in cover layer 122 .
[0191] In another embodiment, the film of the invention comprises the following layer sequence: barrier film / green-emitting polymer layer / barrier film.
[0192] In another embodiment, the film of the invention comprises the following layer sequence: barrier film / intermediate layer / green-emitting polymer layer / intermediate layer / barrier film.
[0193] In another embodiment, the film of the invention comprises the following layer sequence: barrier film / light-emitting polymer layer comprising red and green color conversion materials / barrier film.
[0194] In another embodiment, the film of the invention comprises the following layer sequence: barrier film / green-emitting polymer layer / red-emitting polymer layer / barrier film.
[0195] In another embodiment, the film of the invention comprises the following layer sequence: PET cover layer / green-light-emitting polymer layer / PET cover layer.
[0196] In another embodiment, the film of the invention comprises the following layer sequence: PET cover layer / light-emitting polymer layer comprising red and green color conversion materials / PET cover layer.
[0197] In another embodiment, the film of the invention comprises the following layer sequence: PET cover layer / green-emitting polymer layer / red-emitting polymer layer / PET cover layer.
[0198] In another embodiment, the film of the invention comprises the following layer sequence: barrier film / intermediate layer / green-emitting polymer layer / red-emitting polymer layer / barrier film.
[0199] In another embodiment, the film according to the invention comprises the following layer sequence: intermediate layer / green-emitting polymer layer / red-emitting polymer layer.
[0200] In another embodiment, the film according to the invention comprises the following layer sequence: intermediate layer / green-emitting polymer layer / red-emitting polymer layer / intermediate layer.
[0201] In another embodiment, the film of the invention comprises the following layer sequence: green-emitting polymer layer comprising perovskite crystals / red-emitting polymer layer comprising indium-containing core-shell quantum dots.
[0202] In another embodiment, the film of the present invention comprises the following layer sequence: intermediate layer comprising acrylate polymer or methacrylate polymer / green-emitting polymer layer comprising perovskite crystals / red-emitting polymer layer comprising indium-containing core-shell quantum dots.
[0203] In another embodiment, the film of the present invention comprises the following layer sequence: barrier film / light-emitting polymer layer comprising green core-shell quantum dots containing indium and red core-shell quantum dots containing indium / barrier film.
[0204] In another embodiment, the film of the present invention comprises the following layer sequence: PET film / light-emitting polymer layer comprising green core-shell quantum dots containing indium and red core-shell quantum dots containing indium / PET film.
[0205] Industrial Applicability:
[0206] The color conversion films of the present invention may be assembled to obtain a display backlight assembly. Thus, the present invention also provides a display backlight assembly comprising a color conversion film as described herein.
[0207] The color conversion films of the invention can be assembled to obtain a light emitting device, such as a liquid crystal display. Thus, the invention also provides a light emitting device, preferably a liquid crystal display, comprising a color conversion film as described herein.
[0208] exist Second aspect In the present invention, the present invention relates to a method for manufacturing a color conversion film as described herein. In general, the method comprises the step of applying an atomic layer deposition (ALD) with a plurality of ALD cycles on a plurality of stacked color conversion films 020 in an ALD batch reactor 050. By such an ALD process, an inorganic sealing layer 030 on all edge regions and optionally additionally an inorganic sealing layer 030' on top and bottom film regions is obtained.
[0209] Thus, the present invention relates to a method for manufacturing a color conversion film according to the preceding claims, the method comprising the following steps: (a) providing a plurality of native color conversion films 010' and assembling them into a stack 020; (b) subjecting the stack of step (a) to a first ALD process, thereby obtaining a stack of sealed color conversion films 010; (c) optionally repeating steps (a) and (b), thereby obtaining a multi-sealed color conversion film; (d) optionally subjecting the sealed color conversion film or multi-sealed color conversion films to a finishing step. This will be explained in further detail below.
[0210] In order to effectively seal all four edges 011 ... 014 of the color conversion film (of rectangular shape) with an inorganic layer of very uniform thickness, which completely covers the surface of all four edge regions without pinholes or other defects and completely covers the cracks (also inside the cracks), we found that atomic layer deposition (ALD) is very advantageous. In contrast, conventional chemical and physical vapor deposition methods are disadvantageous because they exhibit directional deposition of inorganic materials, which:
[0211] · prone to shading effects. This means that, for example, cracks or other defects in the edge areas of the color conversion film are not coated uniformly with the inorganic layer (see Figure 2 ), thus allowing oxygen and / or H2O to diffuse into the color conversion film, resulting in edge intrusion.
[0212] Makes it impossible to deposit an inorganic layer with uniform thickness on all four edge regions of the color conversion film in one process step.
[0213] On the other hand, ALD achieves an inorganic layer with uniform thickness on all four edge regions with a single ALD process, and the cracks / defects are completely covered by such a uniform inorganic layer because ALD is not prone to shadowing effects. It is surprising that ALD achieves these positive results in view of the teachings of Nehm et al. cited above.
[0214] Furthermore, a cost-effective ALD batch process was discovered to efficiently deposit uniform inorganic layers on all four edge regions and multiple color conversion films simultaneously. Furthermore, this ALD batch process optionally also allows for additional deposition of such uniform inorganic layers on top and bottom film regions (see Figures 5 to 7 b) This allows making the color conversion film more stable towards oxygen and / or moisture or allows avoiding expensive barrier films (usually inorganic layers present on a PET substrate) during the production of the native color conversion film.
[0215] In view of the above, methods A, B and C set forth below are particularly suitable for obtaining the film 010 of the present invention, which includes a sealing layer 030 providing complete and defect-free edge coverage and optionally an additional sealing layer 030' providing complete and defect-free major surface coverage.
[0216] Method A, see Figure 4 In one embodiment, the color conversion film before the ALD process does not yet include an inorganic sealing layer (i.e., native color conversion film 010') on all four edge regions or top and bottom film regions, and is not coupled to other color conversion films (see Figure 4 ) or a separator film (not shown). This method produces a color conversion film whereby all four edge regions are covered by the inorganic sealing layer 030 after the ALD process, but the top and bottom films are not covered or are substantially not covered. As discussed above, diffusion effects may result in partial coverage of surface areas adjacent to the edges. Such side effects are not shown in the figure and do not negatively impart film properties.
[0217] A separator film (not shown) can be used to avoid direct contact of different color conversion films or to minimize diffusion of ALD precursors into the interface between two color conversion films, thereby minimizing the deposition of inorganic layers on the top and bottom film regions discussed above. Suitable separator films are polymer films or metal films. Preferably, soft polymer films, such as elastic polymer films (e.g., PDMS) or other soft polymer films (e.g., PTFE).
[0218] Method B, see Figure 5 : In another embodiment, the color conversion film before the ALD process does not yet include an inorganic sealing layer on all four edge regions or the top and bottom film regions and is separated by air gaps. This results in a color conversion film 010 whereby all edge regions and the top and bottom film regions are covered with inorganic sealing layers 030, 030' after step b of the ALD process.
[0219] Method C, see Figure 8: The color conversion film of method A is subjected to a further ALD step. In this further step, in stack 020, films 010 are separated by gaps 040 permeable to ALD process gases. The method provides a film 010 of the invention comprising edge seals 030 on all edges and surface seals 030' on both major surfaces and wherein thickness 030>thickness 030'.
[0220] Atomic Layer Deposition (ALD):
[0221] The key feature of the present invention is the implementation of ALD to produce layer 030 (step b) and optionally layer 030' in step (b) or (c).
[0222] Atomic layer deposition (ALD) is a well-known manufacturing method. It must be distinguished from chemical vapor deposition (CVD). (ALD) is a thin film deposition technique based on the sequential use of gas phase chemical processes. In the context of the present invention, the ALD reaction uses two gaseous chemical precursors (also called "reactants"). These precursors react with the material surface one at a time in a continuous, self-limiting manner. By repeatedly exposing to a single precursor, the film is slowly deposited. Therefore, during ALD, the film is grown on the substrate by exposing the substrate surface to alternating gaseous substances (i.e., ALD precursors or ALD reactants, respectively). In contrast to chemical vapor deposition (CVD), the precursors are never present in the reactor at the same time, but they are inserted in the form of a series of continuous, non-overlapping pulses. In each of these pulses, the precursor molecules react with the surface in a self-limiting manner, so that once all the reaction sites on the surface are consumed, the reaction terminates. Therefore, after a single exposure to all precursors (the so-called ALD cycle), the maximum amount of material deposited on the surface is determined by the nature of the precursor-surface interaction. By varying the number of cycles, materials can be grown uniformly and with high precision on arbitrarily complex and large substrates.
[0223] Thus, the ALD fabrication step produces very thin conformal films, and the thickness and composition of the film can be controlled at the atomic level. To determine the thickness of the deposited ALD layer per a specific number of ALD cycles, the ALD layer can be deposited on a silicon substrate, and the layer thickness can then be determined by X-ray reflectometry and ellipsometry.
[0224] In another embodiment, the ALD process is performed at 50° C. to 170° C., preferably 60° C. to 140° C., and most preferably 70° C. to 120° C. Such reaction conditions are believed to be advantageous because of compatibility with the polymer materials present in the film 010 ′.
[0225] In another embodiment, the ALD process is performed at less than 10 mbar, preferably less than 1 mbar, and most preferably less than 0.1 mbar. These conditions allow the reactants to react reliably with the surface in a self-limiting manner.
[0226] The ALD process comprises at least one ALD cycle, typically more than one ALD cycle, whereby one ALD cycle comprises the following steps:
[0227] b1. Introducing the first reactant into the ALD reaction chamber. In this step, the first reactant is adsorbed on the edges 011 ... 014 and optionally on the main surfaces 021, 022;
[0228] b2. Optionally purge the reaction chamber with a purge gas. In this step, the unadsorbed first reactant is removed.
[0229] b3. Introducing the second reactant into the ALD reaction chamber. In this step, the second reactant reacts with the first reactant adsorbed on the substrate.
[0230] b4. Optionally purge the reaction chamber with a purge gas. In this step, the unreacted second reactant is removed.
[0231] In one embodiment, 1 to 100 cycles, preferably 5 to 20 cycles are performed in step b.
[0232] In one embodiment, the first reactant for the ALD process is a metal-containing compound having a molecular weight of less than 500 g / mol, preferably less than 300 g / mol. In another embodiment, the first reactant for the ALD process is selected from the list of metal chlorides, metal alkoxides, metal alkyls, and metal alkylates. In another embodiment, the first reactant for the ALD process is a metal-alkyl, metal-alkoxy, or metal-chloride compound comprising silicon, aluminum, titanium, zirconium, or hafnium, preferably aluminum. In another embodiment, the first reactant for the ALD process is selected from the list of AlCl3, TiCl4, ZrCl4, SiCl4, aluminum isopropoxide, titanium isopropoxide, Al(CH3)3, Ti(CH3)4, Si(CH3)4; preferably Al(CH3)3, Ti(CH3)4, and Si(CH3)4. Such starting materials are commercial items and can be used as purchased.
[0233] In one embodiment, the second reactant is selected from H2O or ozone.
[0234] In another embodiment, the purge gas is nitrogen or CO2, preferably nitrogen. Example
[0235] Comparative Example 1 (unsealed film having a red-emitting layer and a green-emitting layer):
[0236] A color conversion film comprising a green-emitting polymer layer with perovskite crystals and a red-emitting polymer layer with indium-containing core-shell quantum dots was thus produced as described below. This color conversion film did not comprise a sealing layer in the edge region.
[0237] Manufacturing, Comparative Example 1:
[0238] Formulation of the green coating formulation: Formamidine tribromide was synthesized in toluene as follows Green perovskite luminescent crystals composed of lead (FAPbBr3): synthesis of tribromide by grinding PbBr2 and FABr Lead (FAPbBr3). That is, 16mmol PbBr2 (5.87g, 98% ABCR, Karlsruhe (DE)) and 16mmol FABr (2.00g, Greatcell Solar Materials, Queanbeyan, (AU)) were ground together with yttrium stabilized zirconia beads (5mm diameter) for 6 hours to obtain pure cubic FAPbBr3, which was determined by XRD. The orange FAPbBr3 powder was added to oleylamine (80 to 90, Acros Organics, Geel (BE)) (weight ratio FAPbBr3: oleylamine = 100: 15) and toluene (> 99.5%, puriss, Sigma Aldrich). The final concentration of FAPbBr3 was 1 wt%. The mixture was then dispersed by ball milling for a period of 1 hour using yttrium stabilized zirconia beads with a diameter size of 200 μm under ambient conditions (if not otherwise specified, the atmospheric conditions for all experiments were: 35° C., 1 atmosphere, in air) to obtain an ink with green luminescence. 0.1 g of the green ink was mixed with a UV curable monomer / crosslinker mixture (0.7 g FA-513AS, Hitachi Chemical, Japan / 0.3 g Miramer M240, Miwon, Korea) containing 1 wt % photoinitiator diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TCI Europe, Netherlands) and 2 wt % polymer scattering particles (organopolysiloxane, ShinEtsu, KMP-590) in a high-speed mixer and toluene was evaporated by vacuum (<0.01 mbar) at room temperature.
[0239] Formation of the green-emitting polymer layer: The resulting green coating formulation was then coated with a layer thickness of 50 μm on a 25 μm barrier film on one side of the adhesive layer (supplier: I-components (Korea); film structure: PET substrate / SiOx layer / adhesive layer) and then laminated with a 100 μm PET film. Thereafter, the laminate structure was UV-cured for 60 seconds (UVAcube100 equipped with a mercury lamp and a quartz filter, Hoenle, Germany). The initial properties of the film thus obtained showed a green emission wavelength of 526nm, FWHM: 22nm .
[0240] Formation of the red coating formulation: 0.1 g of red emitting crystals of equiaxed core-shell QDs with InP core and ZnS shell (1 wt % suspended in toluene) was mixed with a UV-curable monomer / crosslinker mixture (0.5 g FA-DCPA, Hitachi Chemical Japan / 0.5 g Miramer M2372, Miwon, Korea) containing 1 wt % photoinitiator diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TCI Europe, Netherlands) and 2 wt % polymer scattering particles (organic polysiloxane, ShinEtsu, KMP-590) in a high-speed mixer, and the toluene was evaporated by vacuum (<0.01 mbar) at room temperature.
[0241] Formation of the red emitting polymer layer: The PET film was first peeled off from the green emitting laminate prepared as above. The resulting red coating formulation was then applied to the green emitting polymer layer in a layer thickness of 50 μm and then laminated with a barrier film of the same type as used for the green emitting laminate, whereby one side of the adhesive layer was adjacent to the red emitting polymer layer. Afterwards, the laminate structure was UV cured for 60 seconds (UVAcube 100 equipped with a mercury lamp and a quartz filter, Hoenle, Germany). The initial properties of the film thus obtained showed a red emission wavelength of 1.3 Å. 630nm, FWHM 45nm .
[0242] The film thus obtained was cut into rectangular pieces of 10 cm x 7 cm and had the following structure: barrier film (25 micrometers) - green luminescent layer (50 micrometers) - red luminescent layer (50 micrometers) - barrier film (25 micrometers), wherein no edge seal was applied.
[0243] Comparative Example 2 (PLD edge seal film with red and green light emitting layers):
[0244] A color conversion film was used as in Comparative Example 1. However, this color conversion film did not include a sealing layer on the edge area, which was applied by means of PLD (pulsed laser deposition) technology.
[0245] Manufacturing, Comparative Example 2:
[0246] Application of AlOx edge seal by PLD: On each edge of the film obtained according to Comparative Example 1, an AlOx sealing layer with a thickness of 80 nm was deposited by pulsed laser deposition (PLD). Since this method is a directional deposition, the rectangular film must be processed four times (repositioned after each PLD treatment) in order to apply the AlOx sealing layer on each of the four edges. After the PLD treatment, the stack was disassembled to obtain a 10 cm×7 cm film of the invention, which includes a dense AlOx sealing layer on each of the four edges.
[0247] Test results, comparing examples 1 and 2:
[0248] The stability of the unsealed color conversion film according to Comparative Example 1 and the PLD-sealed color conversion film according to Comparative Example 2 was tested for 500 hours in a climate chamber at 65° C. and 95% relative humidity using rectangular sections of 10 cm×7 cm.
[0249] The average edge intrusion of all four edges was measured for green emission and red emission, respectively. (Red edge intrusion means: the distance from the edge of the film toward the center of the film at which there is no red luminescence or the red luminescence is greatly reduced compared to the center of the film; green edge intrusion means: the distance from the edge of the film toward the center of the film at which there is no green luminescence or the green luminescence is greatly reduced compared to the center of the film).
[0250] In addition, the number of edge intrusion spikes (locally present spots with higher edge intrusion compared to the average edge intrusion over all four edges) is determined by visually inspecting all four edges (edge intrusion spikes can be caused by cracks at the film edge or local barrier film delamination).
[0251] for No Initial film of inorganic edge seal, results after 500 hours at 65°C / 95% rH:
[0252] - Average green edge intrusion on all four edges: 1.5mm
[0253] - Average red edge intrusion on all four edges: 1.0mm
[0254] - Number of edge intrusion spikes on all four edges: cannot be determined because the average edge intrusion is too large.
[0255] for have Results for PLD deposited inorganic edge seal films after 500 hours at 65°C / 95% rH:
[0256] - Average green edge intrusion on all four edges: < 0.1 mm
[0257] - Average red edge intrusion on all four edges: <0.1mm
[0258] -Number of edge intrusion spikes on all four edges: 12
[0259] Conclusion, Comparison of Examples 1 and 2:
[0260] These results indicate that the initial film without the inorganic edge seal exhibits large green and red edge intrusions due to the absence of the edge seal.
[0261] The results also show that the PLD deposited inorganic sealing layer resulted in an average inhibition of green and red edge intrusion, but there were still 12 edge intrusion spikes, indicating the presence of cracks or defects in the edge. This indicates that the edge was not uniformly coated by the inorganic layer applied by PLD, and therefore allowed oxygen and / or moisture to penetrate into the color conversion film at these defect sites.
[0262] Embodiment 1: (of the present invention)
[0263] A color conversion film is prepared as follows, the color conversion film comprising a green-emitting polymer layer having perovskite crystals and a red-emitting polymer layer having core-shell quantum dots containing indium, and the color conversion film is Fringe Domain Including ALD deposited inorganic sealing layers:
[0264] manufacture:
[0265] A stack of 10 color conversion films of Comparative Example 1 (initial films without inorganic edge seals) separated by 200 μm PDMS films was compressed by a fixture and placed in the reaction chamber of an ALD batch reactor. Then, a layer of the color conversion film having a PDMS layer was deposited on the entire stack of the color conversion film by the ALD process described by Nehm et al. (ACS Appl. Mater. Interfaces 2015, 7, 22121-22127). 20nm The ALD deposition process was carried out at 80°C as in Nehm et al. The first reaction gas was electronic grade trimethylaluminum and the second reaction gas was deionized water.
[0266] As a result, all four edge regions are coated with a 20 nm AlOx sealing layer, while the major surface of each color conversion film (except for the topmost color conversion film of the color conversion film stack) does not include an AlOx sealing layer.
[0267] Test results, Example 1:
[0268] The films were subjected to the same degradation tests as in Comparative Examples 1 and 2: have Results obtained for ALD deposited AlOx edge seal films after 500 hours at 65°C / 95% rH:
[0269] - Average green edge intrusion over all four edges: 0mm
[0270] - Average red edge intrusion on all four edges: 0mm
[0271] -Number of edge intrusion spikes on all four edges: 0
[0272] Conclusion, Example 1:
[0273] This result shows that the ALD-deposited AlOx sealing layer effectively blocks the diffusion of oxygen and / or moisture into the color conversion film via the edge region. This indicates that all cracks or other defects are uniformly coated with the AlOx sealing layer, thereby avoiding the formation of edge intrusion spikes at these defect sites. This further shows that the ALD-deposited inorganic sealing layer is advantageous compared to inorganic sealing layers deposited by other directional vapor deposition techniques (such as PLD).
[0274] Example 2 (inventive, ALD deposition on edge and main surface:
[0275] A color conversion film is prepared as follows, the color conversion film comprising a green-emitting polymer layer having perovskite crystals and a red-emitting polymer layer having core-shell quantum dots containing indium, and the color conversion film In the fringe domain and two main surfaces Both include an inorganic sealing layer deposited by ALD:
[0276] manufacture:
[0277] Step A: A color conversion film was prepared according to Comparative Example 1, wherein the two barrier films (comprising SiOx as barrier material) were replaced by two 100 micrometer PET films with adhesive layers. The film thus obtained was cut into rectangular pieces of 10 cm×7 cm and had the following structure: PET layer (100 micrometers)—green-emitting layer (50 micrometers)—red-emitting layer (50 micrometers)—PET film (100 micrometers), wherein no edge seal was applied.
[0278] Then, a 20 nm thick AlOx sealing layer was deposited on the color conversion film stack / stack according to the procedure in Example 1. This resulted in an ALD coated AlOx seal on each of the four edges. (Film 2.A)
[0279] Step B: The ALD treated color conversion film stack is then ALD treated again using the same ALD treatment conditions as in Example 1, except for the following changes:
[0280] - Remove the PDMS separator membrane from the stack.
[0281] - Rotating the edge-sealed color conversion film stack in the ALD chamber so that one side of the color conversion film edge is placed at the bottom of the chamber, thereby aligning the color conversion film vertically.
[0282] - The color converting films were spaced apart from each other to obtain an air gap of about 5 mm between each color converting film, so that the ALD reactants diffused into the air gap and deposited the ALD layer on both major surface areas, ie the top and bottom film areas.
[0283] The resulting ALD treated color conversion film exhibited an AlOx sealing layer on all four edge regions and both the top and bottom film regions. (Film 2.B)
[0284] Test results, Example 2:
[0285] The membranes were subjected to the same degradation tests as above. On all edge areas as well as top and bottom membrane areas all Results for films with an ALD deposited AlOx sealing layer after 500 hours at 65°C / 95% rH:
[0286] - Average green edge intrusion over all four edges: 0mm
[0287] - Average red edge intrusion on all four edges: 0mm
[0288] -Number of edge intrusion spikes on all four edges: 0
[0289] The following color conversion films of this experiment were additionally compared for film brightness degradation after 500 hours at 65°C / 95% rH by measuring brightness values on a blue backlight with a Konica Minolta spectrometer (CS-2000) before and after the stability test:
[0290] - AlOx sealing layer on all edge areas but on top and bottom membrane areas No Color conversion film with AlOx layer → brightness decreases: -65%
[0291] - Color conversion film with AlOx sealing layer on all edge areas and on top and bottom film areas → brightness drop:-8% .
[0292] Conclusion, Example 2:
[0293] These results indicate that the ALD-deposited AlOx sealing layer effectively blocks the diffusion of oxygen and / or moisture into the color conversion film via the edge region. This suggests that all cracks or other defects are uniformly coated with the AlOx sealing layer, thereby avoiding the formation of edge intrusion spikes at these defect sites.
[0294] Furthermore, these results show that the ALD batch process procedure used in this experiment allows for effective sealing of not only the film edges, but also the top and bottom film regions. This avoids the use of expensive barrier films (including inorganic layers) in the fabrication of native color conversion films.
[0295] Comparative Example 3: (Commercial product)
[0296] manufacture:
[0297] A color conversion film containing red and green indium phosphide quantum dots was obtained by disassembling a commercial Samsung TV (model: QN85A, 2021). The red and green quantum dots in the color conversion film exist in a light-emitting polymer layer sandwiched between two inorganic barrier films (barrier film structure: PET substrate / inorganic layer / adhesive layer).
[0298] The stability test was performed on 10 cm x 7 cm films according to the procedure in the previous example. No Initial film of inorganic edge seal, results after 500 hours at 65°C / 95% rH:
[0299] - Average green edge intrusion over all four edges: 1.0mm
[0300] - Average red edge intrusion on all four edges: 1.0mm
[0301] - Number of edge intrusion spikes on all four edges: cannot be determined because the average edge intrusion is too large.
[0302] Example 3: (Improvement of commercial products by ALD deposition on edges)
[0303] manufacture:
[0304] A color conversion film containing red and green indium phosphide quantum dots was obtained by disassembling a commercial Samsung TV (model: QN85A, 2021). The red and green quantum dots in the film are present in a light-emitting polymer layer sandwiched between two inorganic barrier films (barrier film structure: PET substrate / inorganic layer / adhesive layer).
[0305] A stack / stack of 10 such films having a size of 10 cm x 7 cm was subjected to ALD treatment using the same procedure as in Example 1.
[0306] Test results, Example 3:
[0307] for have Results for ALD deposited AlOx edge seal films (invention, Example 3.2) at 65°C / 95% rH after 500 hours:
[0308] - Average green edge intrusion over all four edges: 0mm
[0309] - Average red edge intrusion on all four edges: 0mm
[0310] -Number of edge intrusion spikes on all four edges: 0
[0311] Conclusion, Example 3:
[0312] This result shows that the ALD-deposited AlOx sealing layer effectively blocks the diffusion of oxygen and / or moisture into the color conversion film via the edge region. This indicates that all cracks or other defects are uniformly coated with the AlOx sealing layer, thereby avoiding the formation of edge intrusion spikes at these defect sites.
[0313] It is further shown that commercially available membranes considered to be state of the art are significantly improved by the process of the present invention.
[0314] Summary of embodiments:
[0315] The embodiments provided above can be summarized as follows:
[0316]
[0317]
[0318] The features of the sealing layer 030 on the edge are summarized as follows:
[0319]
[0320] *Nominal thickness as expected by the deposition process used
[0321] **Determined by light microscopy and confirmed by edge invasion / absence of edge invasion.
[0322] With regard to edge intrusion, the results obtained after 500 hours at 65°C / 95% rH are as follows:
[0323] Example Green edge intrusion Red edge intrusion Intrusion spike Comparative Example 1 1.5mm 1.0 ** Comparative Example 2 <0.1mm <0.1mm 12 Comparative Example 3 1.0mm 1.0mm ** Example 1 0 mm 0mm 0 Example 2 0 mm 0mm 0 Example 3 0 mm 0mm 0
[0324] **Cannot be determined because average edge intrusion is too large
[0325] Thus, ALD edge coating solves the problem of edge intrusion and even significantly improves commercial products.
[0326] Regarding the performance, the results obtained after 500 hours at 65°C / 95% rH are as follows:
[0327] Example describe Glowing Down Example 2, membrane 2.A No surface coating on top / bottom -65% Example 2, membrane 2.B ALD surface coating on top / bottom -8%
[0328] Therefore, the ALD surface coating solves the problem of luminescence degradation and is therefore suitable to replace commercial barrier films.
Claims
1. A sealed color conversion film (010), comprising a native color conversion film (010') and one or more sealing layers (30), The native color conversion film (010`) having two main surfaces (021, 022) and at least one edge (011, 012, 013, 014), comprising a color conversion material (80, 100, 200) that emits light in the visible range when excited with blue light; and The sealing layer (030) comprising, preferably consisting of, an inorganic material, and on all edges of the native color conversion film, providing complete and defect-free edge coverage, and has a thickness of 1 nm to 500 nm, preferably 2 nm to 90 nm, and • Have a thickness standard deviation of less than 3% including all edges.
2. The color conversion film according to claim 1, wherein the sealing layer (030) is obtained by an atomic layer deposition process ("ALD process").
3. The color conversion film according to claim 1 or 2, wherein the color conversion film is rectangular in shape, has a top surface and a bottom surface (021, 022) and four edges (011, 012, 013, 014), and meets one or more of the following characteristics: Aspect ratios of 4:3, 3:2, 16:9 or 3:1; Diagonal: 5cm to 250cm; Thickness ranges from 10 microns to 500 microns.
4. A color conversion film according to any one of the preceding claims, comprising • a light emitting polymer layer comprising a green color conversion material (100) and optionally a further light emitting polymer layer comprising a red color conversion material (200); or A light-emitting polymer layer comprising a green color conversion material (100) and a red color conversion material (200); whereby the green color conversion material emits green light when excited by blue light, and The red color conversion material thus emits red light when excited by blue light.
5. The color conversion film according to claim 4, wherein The green color conversion material (100) is selected from the group of perovskite crystals; and The red color conversion material (200) is selected from the group of core-shell quantum dots containing indium.
6. The color conversion film according to any of the preceding claims, wherein the inorganic sealing layer (030) comprises one or more metal oxides or consists of one or more metal oxides; preferably, wherein the inorganic sealing layer (030) comprises the following layer sequence or consists of the following layer sequence: AlO x / MO x , where M = Si, Ti, Zr, Hf.
7. The color conversion film according to any one of the preceding claims, wherein The color conversion film (010) comprises an inorganic seal (030) covering all edges ("edge seal"), but has no or substantially no inorganic coating (030') on its major surfaces; or The color conversion film (010) has, in addition to the inorganic seal (030) ("edge seal") covering all edges, an inorganic seal (030') covering two main surfaces ("surface seal"), and the thickness of the surface seal (030') is lower than the average thickness of the edge seal (030), and the inorganic material of the surface seal (030') is the same as or different from the inorganic material of the edge seal (030); or The color conversion film (010) has, in addition to the inorganic seal (030) ("edge seal") covering all edges, an inorganic seal (030') covering two main surfaces ("surface seal"), wherein the surface seal (030') and the edge seal (030) have substantially the same thickness, and preferably, wherein the inorganic material of the surface seal 030' is the same as the inorganic material of the edge seal (030).
8. The color conversion film according to claim 7, wherein the inorganic surface sealing layer (030') comprises one or more metal oxides or consists of one or more metal oxides; preferably, wherein the inorganic sealing layer (030') comprises the following layer sequence or consists of the following layer sequence: AlO x / MO x , where M = Si, Zr, Ti, Hf.
9. The color conversion film according to any one of the preceding claims, comprising any of the following layer sequences: A green-emitting polymer layer comprising perovskite crystals / a red-emitting polymer layer comprising indium-containing core-shell quantum dots; or • Intermediate layer comprising acrylate polymer or methacrylate polymer / green-light-emitting polymer layer comprising perovskite crystals / red-light-emitting polymer layer comprising indium-containing core-shell quantum dots.
10. The color conversion film according to any of the preceding claims, comprising one or more further layers (070) at the top and / or bottom, said one or more further layers (070) not comprising an inorganic sealing layer (030) at the edge region.
11. A method for producing a color conversion film according to any one of the preceding claims, comprising the following steps: (a) providing a plurality of native color conversion films (010') and assembling them into a stack (020); (b) subjecting the stack of step (a) to a first atomic layer deposition ("ALD") process, thereby obtaining a stack of sealed color conversion films (010); (c) optionally repeating steps (a) and (b) to obtain a multi-sealed color conversion film; (d) optionally subjecting the sealed color conversion film or the multi-sealed color conversion film to a finishing step.
12. The method according to claim 11, wherein in step (a), the stack (020) comprising native color conversion films (010') in direct contact with each other via their major surfaces; or Those including a native color conversion film (010`) separated by an auxiliary separation film; Thereby a color conversion film with an edge seal is obtained.
13. The method according to claim 11, wherein in step (a), the stack (020) comprising a plurality of native color conversion films (010') separated from each other by air gaps; Thereby a color conversion film is obtained having an edge seal and a surface seal, and wherein the edge seal and the surface seal comprise the same material and have the same or substantially the same thickness.
14. The method according to claim 11, wherein in step (c) reassembling the initially obtained stack into an improved stack, wherein the initially obtained color conversion films (010) are separated from each other by air gaps, followed by a second ALD process; Thereby a color conversion film is obtained having an edge seal and a surface seal, and whereby the edge seal layer and the surface seal layer comprise the same or different inorganic materials, and whereby the surface seal layer is thinner than the edge seal layer.
15. The method of any one of claims 11 to 14, wherein the ALD process complies with one or more of the following parameters: The ALD process is performed at 50°C to 170°C; The ALD process is carried out at less than 10 mbar; The first reactant for the ALD process is selected from metal chlorides, metal alkoxides and alkylated metals; The second reactant for the ALD process is selected from H2O and ozone.
16. A color conversion film obtained by the method according to claims 11 to 15, preferably a color conversion film according to any one of claims 1 to 10.
17. A display backlight assembly comprising the color conversion film according to claim 1 to 9 or 16.
18. A light emitting device, preferably a liquid crystal display, comprising the color conversion film according to claim 1 to 9 or 16.
Citation Information
Patent Citations
A solid polymer composition, a self-supporting film and a light emitting device
EP3936585A1
Optical member and display including the same
US20190154901A1
Light guide plate and display device including the same
US20200209463A1
Display device and method of manufacturing the same
US20200251529A1
Light-emitting polymer films, articles containing same, and methods of making
US9470399B1